Integrated Anti-Windup Fault-Tolerant Control Architecture for Optimized Satellite Attitude Stabilization - Ofodile, Ikechukwu; Ofodile-Keku, Nkemdilim; Jemitola, Paul; Anbarjafari, Gholamreza; Slavinskis, Andris (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
This article presents the development of an anti-windup (AW) compensator architecture for nanosatellite systems. The design addresses the problem of fault-tolerant control (FTC) for attitude stabilization subject to actuator saturation, actuator faults, and multiple disturbances. In many practical applications, certain physical limitations in the actuator design often mean that actuator saturation is mostly unaccounted for. Based on the ESTCube-2 nanosatellite model with reaction wheels (RWs), an integrated AW-FTC architecture is designed for an optimized attitude control system. The AW compensator is formulated using the linear matrix inequality (LMI) and computed to generate an augmented solution that is appended to the linear control system. The AW compensator in the architecture is designed with suitable parameters and effective controller gain values. The AW-FTC acts on the RW momentum as control input with the observed torque response, thereby ensuring an asymptotically stable system. Simulation results are presented to demonstrate the effectiveness of this approach with finite-time stabilization under actuator faults and saturation conditions.
Keywords: Actuator fault; anti-windup (AW); attitude control; fault-tolerant control (FTC); nanosatellite; saturation; SPACECRAFT; SYSTEMS; PERFORMANCE; Engineering; Remote Sensing